Butadiene from biomass, a life cycle perspective to address sustainability in the chemical industry. Issue 6 (9th November 2015) - Cespi, D.; Passarini, F.; Vassura, I.; Cavani, F.
Abstract : A multi-criteria approach based on life cycle thinking is proposed to investigate the production of 1, 3-butadiene. Abstract : In the past few decades, innovative approaches such as Green Chemistry and Green Engineering have come out in order to set the basic principles for a more sustainable chemical industry. However, researchers also need a more scientific and quantitative tool to address the sustainability behind the application of those principles. Therefore, a multi-criteria approach based on life cycle thinking was proposed to investigate the production of 1, 3-butadiene. Five indicators were selected to address sustainability: the Cumulative Energy Demand, the carbon footprint, the water depletion, a midpoint-oriented analysis method and an economic index. The use of renewable feedstock was evaluated in comparison with the traditional fossil-based route from naphtha. Two alternative pathways which use bio-ethanol were considered – the Lebedev and Ostromisslensky processes – evaluating the possibility to locate the plant in three different regions (the EU, Brazil and the US). Detailed analysis reveals how the use of bio-based feedstock leads to a significantly lower consumption of fossil sources, despite the higher exploitation of renewable resources leading to larger water withdrawals. Moreover, the assessment of the global warming potential reveals how bio-routes are far from able to be considered carbon-neutral. In addition, the ReCiPe single-score was used, showing greater sustainability of the Lebedev process compared with the traditional way. On the other hand, the two-step pathways (Ostromisslensky) result in the worst scores. An economic evaluation was also applied. The index reveals how the direct conversion into 1, 3-butadiene seems more suitable than the two-step method, particularly in the case of production in the US.